Sex-Related Differences in Lactotroph Tumor Aggressiveness Are Associated With a Specific Gene-Expression Signature and Genome Instability - Wierinckx, Anne; Delgrange, Etienne; Bertolino, Philippe; François, Patrick; Chanson, Philippe; Jouanneau, Emmanuel; Lachuer, Joël; Trouillas, Jacqueline; Raverot, Gérald (Frontiers in Endocrinology, 2018)
Sex-related differences have been reported in various cancers, in particular men with lactotroph tumors have a worse prognosis than women. While the underlying mechanism of this sexual dimorphism remains unclear, it has been suggested that a lower estrogen receptor alpha expression may drive the sex differences observed in aggressive and malignant lactotroph tumors that are resistant to dopamine agonists. Based on this observation, we aimed to explore the molecular importance of the estrogen pathway through a detailed analysis of the transcriptomic profile of lactotroph tumors from 20 men and 10 women. We undertook gene expression analysis of the selected lactotroph tumors following their pathological grading using the five-tiered classification. Chromosomic alterations were further determined in 13 tumors. Functional analysis showed that there were differences between tumors from men and women in gene signatures associated with cell morphology, cell growth, cell proliferation, development, and cell movement. Hundred-forty genes showed an increased or decreased expression with a minimum two-fold change. A large subset of those genes belonged to the estrogen receptor signaling pathway, therefore confirming the potent role of this pathway in lactotroph tumor sex-associated aggressiveness. Genes belonging to the X chromosome, such as CTAG2, FGF13, and VEGF-D, were identified as appealing candidates with a sex-linked dysregulation in lactotroph tumors. Through our comparative genomic hybridization analyses (CGH), chromosomic gain, in particular chromosome 19p, was found only in tumors from men, while deletion of chromosome 11 was sex-independent, as it was found in most (5/6) of the aggressive and malignant tumors. Comparison of transcriptomic and CGH analysis revealed four genes (CRB3, FAM138F, MATK, and STAP2) located on gained regions of chromosome 19 and upregulated in lactotroph tumors from men. MATK and STAP2 are both implicated in cell growth and are reported to be associated with the estrogen signaling pathway. Our work confirms the proposed involvement of the estrogen signaling pathway in favoring the increased aggressiveness of lactotroph tumors in men. More importantly, we highlight a number of ER-related candidate genes and further identify a series of target molecules with sex-specific expression that could contribute to the aggressive behavior of lactotroph tumors in men.